EXAMINING THE MODERATING ROLE OF JOB CONTROL ON WORKLOAD AND EMOTIONAL EXHAUSTION AMONG ACADEMICIANS - Dr. Faisal Khan, Dr. Imtiaz Ahmad, Muhammad Sufyan, Dr. Arab Naz, Dr. Amran Md Rasli (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Academicians face an extensive range of psychosocial stressors; the education sector employees are at a high risk of developing burnout, especially emotional exhaustion, which can affect the quality of their duties and performance. The current researchevaluatesthe moderating effect of job control on the workload and emotional exhaustion relationship. For this purpose, a total of 322 academicians completed self-administrated questionnaires from universities of Khyber Pakhtunkhwa universities. The study finding shows that the paths from the workloadand emotional exhaustion were positive.The analysis illustrates the moderating influence of job controls on the relationship between workload and emotional exhaustion.The study alsodemonstrates the education sector's valuesto carry out management practices that encourage job control and provide employees with resources to reduce risk among employees' exhaustion. The study determines the variables relationships by usingthe JD-R model. Moreover, the study suggested limitations and recommendations to measures at the policy level concerning the work environment